INCLUSION OF CIDR IN OVSYNCH PROTOCOL TO IMPROVE FERTILITY IN POSTPARTUM SUBESTRUS BUFFALOES - KUMAR, K RAVI; ASOKAN, S A; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2023)
Twenty four postpartum subestrus buffaloes not showing observed estrus within 60 days aftercalving were randomly and equally divided into ovsynch-subestrus and ovsynch plus CIDR-subestrusgroups. Ovsynch-subestrus group buffaloes were subjected to ovsynch protocol which consisted of100 μg i.m. injection of GnRH on the day of start of synchronization (d O), 25 mg i.m. injection ofPGF211 seven days later (d 7), another 100 μg i.m. injection of GnRH 48 h after PGF211 (d 9) and timedinsemination 16 to 18 h after second GnRH injection (d 10). Ovsynch plus CIDR-subestrus buffaloeswere subjected to ovsynch plus CIDR protocol which included intra vaginal placement of CIDR devicefor a period of 7 days starting from first GnRH injection ( d O) to PGF 211 injection {d 7) for synchronizationof ovulation. Blood samples were collected from all experimental animals on d -1 O and d 0, d 7, and d9 days after insemination for the estimation of progesterone. During the treatment protocol none of thebuffaloes exhibited visible premature estrus signs. However progesterone estimation showed that 25per cent had exhibited premature estrus. The estrus detection rates were 41.66 and 58.33 per cent inovsynch-subestrus and ovsynch plus CIDR-subestrus respectively. Most buffaloes showed i.ntermediatesigns of estrus. The ovulatory response and first service conception rates were 83.33 and 33.33 and 100 and 41.66 per cent in ovsynch-subestrus and ovsynch plus CIDR-subestrus groups respectively.
Keywords: Ovsynch; CIDR; Subestrus buffaloes; Fertility